Pengaruh Kualitas Pelayanan Penjual Terhadap Keputusan Pembelian Pelanggan pada Daging Ayam Lokal di Pasar Tradisional Kota Bandung - Wibawa, Azkia Putra; Herlina, Linda; Mauludin, Mochamad Ali (Universitas Galuh, 2024)
Traditional markets are one place to sell local chicken meat. Every seller must have a strategy for selling their merchandise to customers in order to be superior to other sellers. One strategy used by sellers is to improve the service quality provided to customers. The aim of this study is to analyze the influence of the service quality on customer’s purchase decision for local chicken meat in Bandung City Traditional Market. The research method is using a survey method with a quantitative approach. The sampling technique in this study is using accidental sampling method by determining the number of samples using the Lameshow formula, totaling 100 people. Data collection was carried out in October – November. The data analysis technique is using simple linear regression analysis. The results show that the service quality variable is in the high category with a percentage of 98% and the purchase decision variable is in the high category with a percentage of 89%. This study shows that seller service quality has a positive and significant influence on customer’s purchase decision for local chicken meat in Bandung City Traditional Market.